Relational analysis of Selected Entrepreneurial Characteristics of Oil Palm Growers with the Level of Adoption - Neelaveni,; P, Venkatarao; Prasad M.V, (Journal of Agricultural Extension Management, 2020)
Oil palm is the crop of present and future vegetable oil economy of world as well as India. The present study was conducted with main objective of studying the farming performance of oil palm growers in terms of level of adoption and entrepreneurial characteristics and how their entrepreneurial characteristics are influencing the level of adoption. Correlation analysis revealed that management orientation, decision making ability, innovativeness, training received, achievement, motivation, information seeking, cosmopoliteness, market orientation, self confidence, value orientation, education, socio economic status, extension contact, socio economic status, education and risk orientation were found positive and significant relationship with extent of oil palm cultivation at 1 per cent level of significance. Leadership status had shown non significant relationship with level of adoption. This paper suggests research, extension and administrative strategies to improve oil palm cultivation